Acute acetate administration increases endogenous opioid levels in the human brain: A [11C]carfentanil molecular imaging study. (May 2021) - Ashok, Abhishekh H; Myers, Jim; Frost, Gary; Turton, Samuel; Gunn, Roger N; Passchier, Jan; Colasanti, Alessandro; Marques, Tiago Reis; Nutt, David; Lingford-Hughes, Anne; Howes, Oliver D; Rabiner, Eugenii A
Introduction: A recent study has shown that acetate administration leads to a fourfold increase in the transcription of proopiomelanocortin (POMC) mRNA in the hypothalamus. POMC is cleaved to peptides, including β-endorphin, an endogenous opioid (EO) agonist that binds preferentially to the µ-opioid receptor (MOR). We hypothesised that an acetate challenge would increase the levels of EO in the human brain. We have previously demonstrated that increased EO release in the human brain can be detected using positron emission tomography (PET) with the selective MOR radioligand [ 11 C]carfentanil. We used this approach to evaluate the effects of an acute acetate challenge on EO levels in the brain of healthy human volunteers. Methods: Seven volunteers each completed a baseline [ 11 C]carfentanil PET scan followed by an administration of sodium acetate before a second [ 11 C]carfentanil PET scan. Dynamic PET data were acquired over 90 minutes, and corrected for attenuation, scatter and subject motion. Regional [ 11 C] carfentanil BP ND values were then calculated using the simplified reference tissue model (with the occipital grey matter as the reference region). Change in regional EO concentration was evaluated as the change in [ 11 C]carfentanil BP ND following acetate administration. Results: Following sodium acetate administration, 2.5–6.5% reductions in [ 11 C]carfentanil regional BP ND were seen, with statistical significance reached in the cerebellum, temporal lobe, orbitofrontal cortex, striatum and thalamus. Conclusions: We have demonstrated that an acute acetate challenge has the potential to increase EO release in the human brain, providing a plausible mechanism of the central effects of acetate on appetite in humans.